Bridging Sustainability and Chemistry Education: A Systematic Review of Problem-Based Learning in Green Chemistry for Enhancing Scientific Literacy - Rani Ratna Kusuma; Rudiana Agustini; Achmad Lutfi; Muhammad Satriawan; Fathimah Soraya (Jurnal Pendidikan MIPA, 2026)
This study aims to identify models for developing teaching materials based on problem-based learning (PBL) in the context of green chemistry and to document the skills reported to have improved in these studies. In addition, this review examines how integrating PBL and green chemistry strengthens science culture, an area where research gaps persist, as previous results have not been systematically summarized. The method used in this study is a Systematic Literature Review (SLR) by following the PRISMA guidelines. Data are obtained from various scientific databases, including Scopus, SINTA, Web of Science (WoS), DOAJ, and Google Scholar, covering publications from 2022 to 2025. A total of 20 peer-reviewed articles that met the criteria were analyzed using a descriptive and bibliometric approach in VOSviewer. The results of the study show that most research reports an improvement in conceptual understanding, critical thinking skills, and environmental awareness when PBL is applied in the context of green chemistry. This approach helps students become aware of environmental issues through relevant problem-solving, such as energy efficiency and the use of environmentally friendly chemicals. The bibliometric analysis highlights five key themes: PBL, green chemistry, scientific literacy, local knowledge, and digital learning, pointing to a growing trend of integrating environmental, cultural, and technological perspectives in research. The thematic synthesis indicates that combining PBL with approaches such as SSI, context-based learning, or ethnoscience can further enhance scientific literacy. This review maps how PBL teaching materials are developed in Green Chemistry and how they relate to scientific literacy. The findings also emphasize the need for quantitative meta-analysis and longitudinal research to examine the long term effects of PBL, a gap not addressed in the 20 reviewed studies. Keywords: systematic literature review, science literacy, green chemistry, problem-based learning.